Analisis Penerimaan Sistem Informasi K Exam Karate Lemkari di Lemkari Sumatera Selatan Dengan Menggunakan Technology Acceptance Model - Maya Sapta Rina Pratama; Rusmala Santi; Fenando Fenando (APTIKOM SUMSEL, 2020)
This study aims to determine the level of acceptance of the K-Exam Lemkari karate system in Lemkari, South Sumatra by using the Technology Acceptance Model (TAM) method. This study uses all the variables in the TAM model. The data in this study were collected using a questionnaire distributed to 236 respondents consisting of black belts and brown belts of Lemkari karate in the cities of Palembang, Muara Enim and Baturaja. Data analysis was performed using simple regression analysis. The results of this study indicate the acceptance rate of the K-Exam system is 73.178%. From this percentage, it can be concluded that the K-Exam system is acceptable and has been used by respondents, namely black belts and brown karate belts. As well as the variable perceived ease of use and attitudes towards using technology have a major effect on the acceptance of the K-Exam information system. The higher the perceived ease of use and attitudes towards using technology, the higher the behavior of using the K-Exam Karate Lemkari information system in Lemkari, South Sumatra